Особливості нагромадження фенольних сполук в експлантатах троянди ефіроолійної в умовах in vitro - Oliynyk, O.O.; Kluvadenko, A.A.; Likhanov, A.F.; Melnychuk, M.D.; Chyzhankova, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
The character of the diffusion of secondary metabolites of Rosa damascena Mill. into the culture medium was studied. The histochemical analysis of intact plants shoots and primary explants on contents of catechins and condensed tannins was carried out. According to the results, it was found that the synthesis of phenolic compounds actively occurs in the living tissues of the primary cortex and the medullary rays of annual shoots, where their concentration is 15–18 times higher than in the cells of sclerenchyma and phloem. The phenolic compounds were segregated actively – by primary explants of Lada variety, less actively by explants of Lan variety. It was shown that the intensity of the excretions of phenols from the stem into the culture medium had a spatial in homogeneity of the tissue that is topologically related to the arrangement of vegetative buds. It was found that the most active in this regard were the primary cortical zones directly located below buds. It was determined that the intensity of secondary metabolites excretions depended on the type of Rosa damascena, the radial dimension and the degree of explants woodiness.